2013
DOI: 10.6002/ect.2012.0295
|View full text |Cite
|
Sign up to set email alerts
|

Chronotropic Incompetence on Dobutamine Stress Echocardiography in Candidates for a Liver Transplant

Abstract: Objectives: We evaluated dobutamine stress echocardiography as an initial screening test for a cardiac evaluation before a liver transplant. Materials and Methods: We retrospectively examined 111 liver transplant candidates who had undergone previous cardiac evaluation; 30 of whom had undergone a liver transplant. Results: Eighty patients (72.1%) completed a dobutamine stress echocardiography (41 chronotropically competent, 39 incompetent), while 31 patients (27.9%) required us to terminate early. Overall, 68 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 28 publications
(33 reference statements)
0
14
0
3
Order By: Relevance
“…DSE is only reliable if at least 85% of the predicted maximum heart rate is achieved. However, 19%‐50% of patients do not achieve this due to the use of beta‐blocking agents, peripheral vasodilatation, and chronotropic incompetence . Recent data suggest that β‐blockers can be temporally discontinued without hemodynamic rebound or increased variceal bleeding .…”
Section: Assessment Of Coronary Artery Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…DSE is only reliable if at least 85% of the predicted maximum heart rate is achieved. However, 19%‐50% of patients do not achieve this due to the use of beta‐blocking agents, peripheral vasodilatation, and chronotropic incompetence . Recent data suggest that β‐blockers can be temporally discontinued without hemodynamic rebound or increased variceal bleeding .…”
Section: Assessment Of Coronary Artery Diseasementioning
confidence: 99%
“…Recent data suggest that β‐blockers can be temporally discontinued without hemodynamic rebound or increased variceal bleeding . In addition, DSE is not without complications, and early termination rate due to significant changes in blood pressure, arrhythmia, and chest pain are reported in up to 28% of patients …”
Section: Assessment Of Coronary Artery Diseasementioning
confidence: 99%
“…However, this meta-analysis found much lower sensitivity values for diagnosis of CAD in patients awaiting LT, while specificity rates did not vary so much. This could have happened because results for stress testing might be false due to modifications in hemodynamics caused by ESLD, such as high-output cardiac failure, cirrhotic cardiomyopathy, anemia and the use of beta blockers[ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 While much speculation has resulted in identifying the best approach to exclude clinically significant CAD, current guidelines recommend noninvasive testing, including dobutamine stress echocardiography (DSE). 1,[3][4][5][6][7][8] Although the sensitivity and specificity of this study compared to invasive angiography can be limited in the endstage liver disease (ESLD) population, its results tend to be a strong predictor of clinical outcomes. [7][8] As part of stress testing, a continuous dobutamine infusion and, frequently, atropine adjunctive therapies are administered in order to achieve a target heart rate to allow for an accurate assessment.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][10][11][12][13][14][15][16] These properties can make it more difficult to achieve an adequate heart rate response, requiring the use of atropine as an adjunct to dobutamine during testing. [4][5][6] Although atropine has been shown to be relatively safe in the general population, its anticholinergic effects can result in the development of adverse symptoms, including worsening encephalopathy. Wuthiwaropas et al found that in a prospective study of 1006 patients undergoing DSE with atropine use, the administration of at least 1 mg atropine resulted in a more than 5-fold increase in neuropsychiatric symptoms.…”
Section: Introductionmentioning
confidence: 99%